Wine Ratings: Seeking a Consensus among Tasters via Normalization, Approval, and Aggregation. (August 2021) - Gergaud, Olivier; Ginsburgh, Victor; Moreno-Ternero, Juan D.
Abstract: The modern era of wine journalism has provided abundant information about wines and widespread use of numerical rating systems. A tiny difference, especially at the top of the distribution of ratings, may have striking consequences on wine sales and investment returns. This article provides a general framework to obtain a consensus among tasters' opinions (reflected as numerical wine ratings) via three subsequent stages: normalization, approval, and aggregation . It is inspired by contributions in political science, social choice, game theory, and operations research. We apply it to the Judgment of Paris as well as to rank 2018 en-primeur Bordeaux wines, rated by five international experts. (JEL Classifications: C18, L15, L66)